TINJAUAN YURIDIS IMPLEMENTASI UANG PAKSA (DWANGSOM) DI PERADILAN TATA USAHA NEGARA - Bambang Heriyanto (Jurnal Hukum Peratun, 2021)
The procedural law of the administrative court regulated in Law no. 5 of 1986 concerning the Administrative Court as the latest change in Law no. 51 of 2009 concerning the Second Amendment to Law no. 5 of 1986 concerning the State Administrative Court (Law on the State Administrative Court) stipulates that there is a forced effort to execute the decision of the state administrative court, one of which is in the form of forced money (dwangsom). However, the problem in its implementation is that there are no laws and regulations that regulate the procedure for imposing forced money and regarding the amount so that in practice there are still very few courts that apply forced money as an effort to force the implementation of state administrative court decisions. This paper attempts to provide an overview and solutions to these problems, including providing a comparative picture of the regulation of forced money in several countries. The writing method used is a legal-normative method, namely by using library data related to forced money in state administrative courts, and related laws and regulations.